Crafting animated parables: an embodied approach to representing lifestyle behaviours for reflection. Issue 1 (2nd January 2021) - Chow, Kenny K. N.
ABSTRACT: Latest work regarding personal informatics, gamification, and feedback has suggested that visualizing behavioural data for daily reflection should consider dynamic representations in metaphors and narratives with positively and negatively valued outcomes. Grounded in behavioural models from social psychology and embodied cognition theories, this article proposes a framework guiding the generation of animated parables wherein causality between a behaviour and its virtual outcomes is easy to understand. The guidelines include metaphorical mapping and blending the behaviour with a direct cause-effect scenario with similarities in embodied experiences. Application of the guidelines in a series of design workshops generates 47 parables. To evaluate the parables, metrics include naturalness of integrating with life routines, aesthetics of blending into environments, and ease of interpreting the causality. Evaluation results show that more embodied mapping and blending are more likely to result in understandable behaviour-outcome links. Designers can follow the guidelines and metrics to generate and compare ideas. Lastly, recommendations for crafting more embodied parables are provided.